The Impact of Secondary Schooling in Kenya : A Regression Discontinuity Analysis - Ozier, Owen (World Bank, Washington, DC, 2015)
This paper estimates the impacts of secondary school on human capital, occupational choice, and fertility for young adults in Kenya. The probability of admission to government secondary school rises sharply at a score close to the national mean on a standardized 8th grade examination, permitting the estimation of causal effects of schooling in a regression discontinuity framework. The analysis combines administrative test score data with a recent survey of young adults to estimate these impacts. The results show that secondary schooling increases human capital, as measured by performance on cognitive tests included in the survey. For men, there is a drop in the probability of low-skill self-employment, as well as suggestive evidence of a rise in the probability of formal employment. The opportunity to attend secondary school also reduces teen pregnancy among women.